Classroom Interaction analysis by using SETT (Self Evaluation Teacher Talk) - Abdullah Yusuf (STKIP AL HIKMAH SURABAYA, 2025)
Effective classroom interaction plays a crucial role in facilitating language learning by balancing teacher control and student participation. One widely recognized framework for analyzing teacher talk is Steve Walsh’s Self-Evaluation of Teacher Talk (SETT) framework. Overall, the teacher’s talk aligns well with SETT principles, ensuring clear structure, active participation, and balanced focus on meaning and form. The integration of cultural and religious elements contributes to a comfortable learning atmosphere, while the scaffolded tasks effectively guide students through language use. By increasing student-led interaction, early target language use, and critical thinking opportunities, the lesson could become even more effective in fostering learner independence and communicative